Spider silk processing for spidroin recovery from crossopriza lyoni web - Mohtar, Johan Ariff; Ooi, W. L.; Yusof, Faridah (2018)
Spider silk is a potential biomaterial that can be used in various applications for its outstanding physicomechanical properties attributed by the spidroin composition. Efforts for commercializing spider silks have been mainly focused on the characterization of spidroins from the Entelegyne spiders for exceptional fibre construction. Hence, studies on silk proteins from the Haplogyne species remain neglected. The aim of this study is to isolate spidroin from Crossopriza lyoni web. Silk processing involved the pretreatment of fibres for the shell layer removal from the surface. A screening study was conducted to analyze the effect of temperature, incubation time and agitation speed on spidroin extraction using Ajisawa's reagent by OFAT analysis followed by statistical optimization of the extraction process via RSM for maximal protein recovery. All parameters exerted significant effect on spidroin recovery (p<0.05) in which the maximum protein concentration (451.78 ± 0.110 μ g/ml) was obtained at optimal condition of 70°C, 350 rpm and 1.25 hours. The discovery of spidroin from this study provides a basic platform for engineering spider silk to meet the demand for a variety of silk-based products in the near future.